Karakterisasi Agronomi dan Morfologi Aksesi Padi Lokal Asal Kecamatan Rumbio Jaya dan Kecamatan Kampar Kabupaten Kampar - Fauziah Mayasari; Fetmi Silvina; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to find out the diversity of agronomic and morphological characters of various local rice accessions obtained from two Districts in Kampar Regency namely Rumbio Jaya District and Kampar District. The research was conducted at the Faculty of Agriculture, Universitas Riau on September 2017 to March 2018. The research used descriptive analysis method which consists of characterization referring to the guidelines for the characterization and evaluation system of rice plants. The results of the research shows that there are diversity between accessions in the form of agronomic and morphological characters, where the characterization is carried out on 10 observational characters including plant age, plant height, grain fertility, pistil head color, stem color, leaf neck color, leaf ears color, leaf stem color , leaf tongue shape and number of tillers. This information is useful for plant breeders in developing superior varieties of Kampar local rice plants. In addition, this information is useful as a historical description of the collected accession.Keywords: Characterization, accession, local rice plant, kampar regency